2022
DOI: 10.4236/fns.2022.1311063
|View full text |Cite
|
Sign up to set email alerts
|

Development of Functional Synbiotic Flavored Fermented Skim Milk Drinks Supplemented with Doum (<i>Hyphaene thebaica</i> L.) and Carob (<i>Ceratonia siliqua</i>) Fruits Powder for Nutritional, Antimicrobial and High Antioxidant Activities

Abstract: The present study was carried out to make new healthy synbiotic flavored fermented skim milk drinks (SFFSD) supplemented with either Doum (Hyphaene thebaica L.) or Carob (Ceratonia siliqua) fruits powder for nutritional, antioxidant and antimicrobial activities. The HPLC analysis showed higher phenolic and flavonoid content in Doum extract than that of Carob. The antimicrobial activity of the methanolic extracts of both Doum and Carob against foodborne pathogens showed that the most sensitive indicators were B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…QE/mg) of mesocarp farm 70 %. These results agreed with those reported byKhider et al (2022), who found (51.436-67.540 mg QE/g). While the total flavonoid content of mesocarp farm 100 % water extract was the lowest (26.22 mg QE/g), which was a result of the water extract, the ethanol extract of doum palm fruits is higher than doum palm water extract in total flavonoids content reported byAamer (2016).…”
supporting
confidence: 94%
“…QE/mg) of mesocarp farm 70 %. These results agreed with those reported byKhider et al (2022), who found (51.436-67.540 mg QE/g). While the total flavonoid content of mesocarp farm 100 % water extract was the lowest (26.22 mg QE/g), which was a result of the water extract, the ethanol extract of doum palm fruits is higher than doum palm water extract in total flavonoids content reported byAamer (2016).…”
supporting
confidence: 94%
“…Phenolic profiling of edible parts Hyphaene thebaica (Doum palm) are identified using LC-ESI-MS by Hussiena et al (2021), twenty three isolated compounds were identified as ; Caffeic acid, protocatechuic acid, rhamnetin, catechin, quercitrin, vanillic acid, kaempferol 3-O-acetyleglucoside , cinnamic acid, apigenin-7-O-glucose , intricatin-3-O-htyrosol, luteolin, quercetin, naringenin , kaempferol ,vanillic acid-4-β-D-glycoside coumaric acid, ferulic acid, luteolin-6-arbinose-8glucose, p-coumaroyl malic acid eriocitrin, apigenin and hesperetin. Khider et al (2022) study shows that Doum fruit has more antioxidant and more antimicrobial effect. Also, Doum exhibit high content of minerals which increases the nutritional value.…”
Section: Reviews On Doum Palm (H Thebaica)mentioning
confidence: 82%